1982
DOI: 10.1139/e82-143
|View full text |Cite
|
Sign up to set email alerts
|

Conductive structures in southwestern Canada: a regional magnetometer array study

Abstract: An array of 33 three-component recording magnetometers was operated in June and July 1980 in Alberta and British Columbia south of the Edmonton – Prince Rupert highway. This very large array, with its stations dispersed through 550 000 km2 and on average 150 km apart, had limited resolution and was designed to confirm known conductive structures, discover new ones, and locate them sufficiently for suitable placement of further arrays with closer spaced stations and, therefore, higher resolution. Magnetograms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…From these facts, we conclude that the observed pervasive high conductivity in the region is due to some form of mineralization (possibly copper sulphide), rather than due to brines or graphite. (6) This investigation confirms the presence of the Rocky Mountain trench conductor that was postulated earlier by Gough et al (1982), Hutton et al (1987), and Gupta and Jones (1990). As shown in Fig.…”
supporting
confidence: 86%
“…From these facts, we conclude that the observed pervasive high conductivity in the region is due to some form of mineralization (possibly copper sulphide), rather than due to brines or graphite. (6) This investigation confirms the presence of the Rocky Mountain trench conductor that was postulated earlier by Gough et al (1982), Hutton et al (1987), and Gupta and Jones (1990). As shown in Fig.…”
supporting
confidence: 86%
“…A large-scale geomagnetic depth sounding (GDS) magnetometer array study in 1980 (Gough et al 1982) confirmed both the validity of approximating the gross regional structure by a 2-D model and the existence of a zone of anomalously high conductivity beneath much of the Canadian cordillera, named the Canadian Cordilleran Regional (CCR) conductor by Gough (1986a). A large GDS array in the north-western US states, operated as part of the EMSLAB project (EMSLAB 1988;Booker & Chave 1989).…”
Section: I T H O P R O B E Southern C O R D I L L E R a M T S U R Vmentioning
confidence: 91%
“…The lithosphere was modeled at 1,000 Ωm (Trichtchenko et al, 2019). The second model, shown in Figure 8, was identical to the first, but also included a northeast-southwest trending 1 Ωm conductor to represent the SABC in south-central Alberta between 20 and 30 km depth based on Gough et al (1982), Nieuwenhuis et al (2014) and Wang (2019) (Figure 8). Note, that in both models, ocean bathymetry was included in padding cells with ocean model cells set to 0.3 Ωm.…”
Section: The Cause Of Geoelectric Field Polarization In Southern Albertamentioning
confidence: 99%